Total synthesis and preliminary SAR study of (±)-merochlorins A and B. Issue 1 (26th October 2015) - Yang, Hongzhi; Liu, Xue; Li, Qingong; Li, Longbo; Zhang, Jing-Ren; Tang, Yefeng
Abstract : A modular synthesis of merochlorins A and B, two naturally occurring antibiotics, has been achieved from the readily available building blocks in a highly concise manner. Abstract : A modular synthesis of merochlorins A and B, two naturally occurring antibiotics, has been achieved concisely from readily available building blocks in 4–6 steps. The key steps include the bio-inspired tandem phenol oxidative dearomatization/[5 + 2] and [3 + 2] cycloadditions to construct the tricyclic cores of the targets, and the intermolecular Diels–Alder reaction followed by dehydrogenative aromatization to assemble the remaining aromatic units. The antibacterial activities of merochlorins A, B and some advanced synthetic intermediates were also evaluated, which provided valuable information on the structure–activity relationship (SAR) of this class of new antibiotics.